Club Convergence in the Eurozone: a Look at Inequality Dynamics - Vale, S. (47th EBES Conference, 2024)
This paper analyses the convergence of inequality indicators across eurozone countries between 1995 and 2019. The Phillips and Sul (2007, 2009) methodology is applied, testing for the existence of convergence clubs. Our results indicate that eurozone countries share a common path with respect to the income of the richest 1% of the population, and can be grouped into two clusters regarding all other indicators.